Roland Barthes, Guy Debord and the Pedagogical Value of Creative Liberation - Hammond, Craig A (PRISM: Casting New Light on Learning, Theory and Practice, 2018)
The flexible remit of this article should operate as an invitation for educational practitioners to consider and hopefully engage with a range of democratic and malleable pedagogical tactics, and ways in which they might be adapted across academic and curricular practices within and across Higher Education. As such, the article does not present a specific and robustly complete set of pedagogical models, replete with pre-assigned instructions for an exact and replicative application. Rather, the brief tract should operate to incite and generate thoughts and ideas relating to new and alternative possibilities; and, in doing so, nudge new and insurgent ways of engaging with knowledge, the Higher Education environment, and the student experience. Through the exploration of a range of ideas and concepts, (adapted from the work of Roland Barthes and Guy Debord - specifically the Death of the Author, and the dérive and détournement), the piece argues that Higher Education academics and lecturers need to creatively confront the debilitating values and excesses of consumption – currently sweeping universities – with an insurrectionary range of radical tactics and alternative practices.